Agroforestry systems: A teaching and learning strategy (Research, Society and Development, 2023)
The Agroforestry project (SAF) is an important teaching and learning strategy, as it is characterized as an interdisciplinary pedagogical practice with the aim of bringing together different themes from different curricular components. However, there is little research on the use of SAFs in the teaching-learning process. The objective was to verify the perception of students in technical courses integrated into high school in the natural resources technological axis regarding the use of SAF as an educational space to carry out integrative practices and the impact on the teaching-learning process. Research was approved by the Ethics Committee of the State University of Amapá (UEAP) under opinion number 5.376.570. Target audience for the research were students from integrated secondary technical courses in agriculture and agroecology at IFAP Campus Agrícola Porto Grande. 31 questionnaires were administered in person. Data was compiled and underwent descriptive analysis and cluster analysis for some variables. It was found that SAFs can be used as a pedagogical tool in the teaching-learning process as they allow interaction between the subjects of the curriculum, strengthening the importance of knowledge about the environment and family farming which enriches the teaching-learning process.